Community Empowerment by Training Health Cadres and Distributing T-shirts with New Normal Adaptations - Trisna, Citra; Aminah, Aminah (POLTEKKES KEMENKES BANTEN, 2023)
Covid-19 cases occur in almost all countries in the world, including Indonesia. One of the cities with high Covid-19 cases is Tangerang. Data on Covid-19 cases in RW 13, Gebang Raya Sub-district, Tangerang City, obtained a total of 48 confirmed cases in the sub-district, 28 people recovered and 4 (four) people died. The problems faced by the people of Rw 13 Gebang Raya Village are an increase in Covid-19 cases, and the death of four people. The purpose of this community service is to train community leaders and cadres as an extension of the Poltekkes Kemenkes Banten, to increase knowledge and change the behavior of the surrounding community in order to change habits according to the new normal adaptation, so that the chain of transmission of this disease can be broken. The implementation of this community service activity uses the service method, namely community education. Activities carried out in the form of informative and educative counseling to the community directly with the following details: a). Target group survey, b). Identification of Program Needs, and c). Preparation of Facilities and Infrastructure, The implementation of the activity was carried out for two days, namely on 17 and 18 October 2020, at RW 13, Gebang Raya Village, Periuk District, Tangerang City. The evaluation was carried out on November 17, 2020. The data was obtained from the results of the pretest and posttest and discussions with participants. The results obtained were an increase in knowledge, attitudes and behavior after training in the form of counseling and an agreement was produced that community leaders and cadres who had been trained would convey it to other communities.